2003
DOI: 10.1159/000071268
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Relaxes Rat Aorta via Endothelium-Dependent and -Independent Mechanisms

Abstract: The effects of estrogen on arterial function are heterogeneous with respect to vessel and/or species. We have investigated 17β-estradiol-induced relaxation in isolated rat aorta with regard to the role of the vascular endothelium and ionic mechanisms. Estrogen induced a concentration-dependent relaxation of 46.5 ± 7.9% and 70.1 ± 12.2% (10–8 and 10–7M), which was reduced by endothelial denudation. Furthermore, L-nitroarginine methyl ester completely abrogated this effect; however, estradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…It is important to note, however, that the effective concentrations of 2-ME in our in vitro experiments are considerably higher than the picomolar to tens of nanomolar concentrations found in normal human plasma (6). The effective concentrations of 2-ME for the inhibition of PE-induced contraction observed in the present in vitro study lie in the micromolar range, i.e., similar to the effective concentrations of estrogen for the inhibition of contraction reported by others (1,4,16,24,32). These concentrations are also consistent with those required for the 2-ME induction of antiproliferative activity in cultured cells (5,12,22,38).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It is important to note, however, that the effective concentrations of 2-ME in our in vitro experiments are considerably higher than the picomolar to tens of nanomolar concentrations found in normal human plasma (6). The effective concentrations of 2-ME for the inhibition of PE-induced contraction observed in the present in vitro study lie in the micromolar range, i.e., similar to the effective concentrations of estrogen for the inhibition of contraction reported by others (1,4,16,24,32). These concentrations are also consistent with those required for the 2-ME induction of antiproliferative activity in cultured cells (5,12,22,38).…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, if the endothelium is absent, E 2 can directly inhibit smooth muscle contraction independent of NO production. Endothelium-dependent and -independent mechanisms have been previously found in E 2 -induced relaxation of aortic rings (1,21). Importantly, the present study demonstrated that 2-ME inhibited smooth muscle contraction at concentrations similar to the effective concentrations of E 2 on inhibition of contraction as reported by others (10, 16, 21, 32).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These include studies on isolated arteries from rats (aorta, coronary, and mesenteric arteries; see Refs. 1,36,39,48), rabbit carotid artery (46), mouse aorta (13), coronary microvessels from female or male dogs (24), and human vessels, including coronary arteries (11) and from our laboratory small subcutaneous arteries from men (unpublished data). In contrast, others have implied that NO plays a role in the acute dilation to 17␤-E 2 in, for example, isolated female coronary arteries (4,11), aorta and femoral arteries from rat (5, 51), human mammary artery (38), rabbit coronary artery, and uterine arteries from sheep (44,55).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these consensus sites is consistent with evidence showing that levels of eNOS transcripts are elevated by sheer stress (Davis et al, 2001; Woodman et al, 2005), exercise (Sessa et al, 1994; Yang et al, 2002) and hypoxia (Le Cras et al, 1996). Regulation of eNOS transcription by estrogens is still a matter of debate (Arnal et al, 1996; Kleinert et al, 1998), however, estradiol relaxes rat aortic segments via endothelium-dependent and -independent mechanisms involving the NO-cGMP signaling system (Abou-Mohamed et al, 2003). Both lipopolysaccharide (Arriero et al, 2000) and tumor necrosis factor-α (Yoshizumi et al, 1993) decrease eNOS gene expression by reducing the stability of eNOS mRNAs.…”
Section: Transcriptional and Post-transcriptional Regulation Of Enos mentioning
confidence: 99%